Gejala Klinis Neurologis dan Gambaran CT Scan Otak Pasien Kanker Paru Karsinoma Bukan Sel Kecil Metastasis ke Otak di Rumah Sakit Persahabatan - YULIANTI, DIAN; SYAHRUDDIN, ELISNA; HUDOYO, AHMAD; ICKSAN, AZIZA (Indonesian Journal of Cancer, 2010)
Brain is one of the common sites of distant metastasis in patients of lung cancer, and incidens of brain metastasis in lung cancer is considered high. In Non-small Cell lung cancer guide line, brain CT done if the neurological symptom occured. Therefore analysis of diagnostic approach related to brain metastases is needed. Prospective analysis of 35 patients newly diagnosed cases of brain metastases in NSCLC. Cross sectional study with additional analysis to find relationship of clinical symptom to result of CT brain over periode July 2008-August 2009 in Persahabatan Hospital. Data were analysed as regards to the presence/absence of neurogical symtomps. Prognostic approach was applied to analyze survival rate.We found that 85,7% patients brain metastases with neurological symptomatic and 14,3% asymptomatic. Five (14,3%) patients with more than one neurologycal symptoms. Depend on stage and cell type of which 27 (77,1%) with adenocarcinoma, 21 (62,9%) with T4, 17 (48,6%) N0 and patients with soliter nodule 8 (22,9%). Thereâs no correlation between neurologycal symptom and brain metastases. Median survival time of lung cancer patients with brain metastases are 11 month. The majority lung cancer patients with brain metastasis have neurological symptoms. The most brain metatases found in patient with adenocarcinoma, T4 and N0. Median survival was increased in treated patients Keywords: Lung cancer, NSCLC, Brain metastases, Neurological symptoms